Էլեկտրաէներգիայի ոչ տեխնիկական կորուստների գնահատում - Արամ Համայակի Առաքելյան; Ստյոպա Սամվելի Ծառուկյան (ՀՀ ԳԱԱ հրատ.)
В настоящее время в большинстве стран и в частности в Армении, расход электроэнергии определяется по показанию счетчика электроэнергии оператором энергосети. Однако такой способ регистрации расхода электроэнергии чреват обманом со стороны оператора и потребителя,который может отнести свои расходы на показания счетчика электоэнергии других потребителей. Представляемая работа посвящена изучению проблемы оценки риска потребителей электроэнергии на основе модели оценки риска Пратта. Currently, in many countries and particularly in Armenia, the cost of electricity consumption is determined by the meter of the electricity meter from grid operator. However, such a method of recording the electricity consumption causes fraud by a dishonest consumer or by the operator of the grid, thus resulting in adding some additional amount to the original bill to be paid by honest consumers. The article proposes a model for calculating the cost of consumed electricity based on which the risks associated with honest and dishonest consumers are computed according to Pratt.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ